Biochemical and Cell Biological Assays to Identify and Characterize DNA Helicase Inhibitors - Banerjee, Taraswi (Methods, 2016)
The growing number of DNA helicases implicated in hereditary disorders and cancer indicates that this particular class of enzymes plays key roles in genomic stability and cellular homeostasis. Indeed, a large body of work has provided molecular and cellular evidence that helicases act upon a variety of nucleic acid substrates and interact with numerous proteins to enact their functions in replication, DNA repair, recombination, and transcription. Understanding how helicases operate in unique and overlapping pathways is a great challenge to researchers. In this review, we describe a series of experimental approaches and methodologies to identify and characterize DNA helicase inhibitors which collectively provide an alternative and useful strategy to explore their biological significance in cell-based systems. These procedures were used in the discovery of biologically active compounds that inhibited the DNA unwinding function catalyzed by the human WRN helicase-nuclease defective in the premature aging disorder Werner Syndrome. We describe in vitro and in vivo experimental approaches to characterize helicase inhibitors with WRN as the model, anticipating that these approaches may be extrapolated to other DNA helicases, particularly those implicated in DNA repair and/or the replication stress response.